Magnetically-induced rotating Rayleigh-Taylor instability - Scase, Matthew M.; Baldwin, Kyle A.; Hill, Richard J.A. (Journal of Visualized Experiments, 2016)
Classical techniques for investigating the Rayleigh-Taylor instability include using compressed gasses, rocketry or linear electric motors to reverse the effective direction of gravity, and accelerate the lighter fluid toward the denser fluid. Other authors have separated a gravitationally unstable stratification with a barrier that is removed to initiate the flow. However, the parabolic initial interface in the case of a rotating stratification imposes significant technical difficulties experimentally. We wish to be able to spin-up the stratification into solid-body rotation and only then initiate the flow in order to investigate the effects of rotation upon the Rayleigh-Taylor instability. The approach we have adopted here is to use the magnetic field of a superconducting magnet to manipulate the effective weight of the two liquids to initiate the flow. We create a gravitationally-stable two-layer stratification using standard flotation techniques. The upper layer is less dense than the lower layer and so the system is Rayleigh-Taylor stable. This stratification is then spun-up until both layers are in solid-body rotation and a parabolic interface is observed. These experiments use fluids with low magnetic susceptibility, |χ| ~ 10^6 — 10^5, compared to a ferrofluid. The dominant effect of the magnetic field is to apply a body force to each fluid layer changing the liquid’s effective weight. The upper layer is weakly paramagnetic and the lower layer is weakly diamagnetic so that as the magnetic field is applied, the lower layer is repelled from the magnet while the upper layer is attracted toward the magnet. The upper layer behaves as if it is heavier than it really is, and the lower layer behaves as if it is lighter than it really is. If the applied gradient magnetic field is large enough, the upper layer may become “heavier” than the lower layer and so the system becomes Rayleigh-Taylor unstable. and we see the onset of the Rayleigh-Taylor instability. We further observe that increasing the dynamic viscosity of fluid in each layer increases the observed lengthscale of the instability.